Clinical and anatomical traits of orthopaedic traumatic and maxillofacial osteomyelitis: a systematic review - S. V. Baranov; A. R. Usnunts; A. B. Zaytsev (Кубанский научный медицинский вестник, 2021)
Background. Chronic osteomyelitis requires a multidisciplinary approach. The main contributors are physicians of two specialties, orthopaedic trauma and maxillofacial surgeons, depending on the pathology’s localisation. Each specialty often relies on its own research and experience, whereas a cross-disciplinary assessment of same pathology allows a broader perspective of the problem.Objectives. A comparative survey of orthopaedic trauma and maxillofacial evidence on the aetiology, pathogenesis and treatment of osteomyelitis for effective sharing and leveraging of practices.Methods. The review generalizes relevant publications on the etiopathogenesis and treatment of osteomyelitis of various location in different patient profiles indexed in the PubMed, Science-Direct and eLIBRARY databases from January 2014 till June 2020. The keyword queries were: osteomyelitis jaws [остеомиелит челюстей], osteomyelitis mandible maxilla, osteomyelitis lower limb [остеомиелит нижних конечностей], osteomyelitis microbiology antibiotic therapy [остеомиелит микрофлора]. We conducted historical and bibliometric analyses of domestic and foreign scientific archives on general and special issues in anatomy, aetiology, pathogenesis and treatment of chronic osteomyelitis of various location.Results. The working ability and social adaptation are recovered in chronic osteomyelitis patients via a multicomponent process, which includes conservative therapy, surgical treatment and rehabilitation measures.Conclusion. Main aetiological and pathogenetic traits of chronic osteomyelitis of various location can be used to lay out interdisciplinary tactics in purulent necrotic surgery utilising various materials and methods for function restore.